Contempt of Court in Renewal of Indonesian Criminal Law Based on Pancasila - M Musmuliadin; Erlyn Indarti; Nur Rochaeti (Proceeding International Conference Restructuring and Transforming Law, 2022)
The act of harassment against the administration of justice is not new. However, these acts have been happening more frequently since the freer reform era. Actions and situations that occur in court such as obstructing and making noise during the trial process can be said to be Contempt of Court ("CoC") acts. CoC does not only apply to those who are not court officials but also applies to court officials in carrying out their duties and obligations. To see and analyze the Contempt of Court issue, it is necessary to know how the criminal law policy is in tackling offenses against the administration of this judiciary and how the concept of the Draft Criminal Code regulates it. To answer this question, in Point 4 Elucidation of Law No. 14 of 1985 the Supreme Court of the Republic of Indonesia has stated the need for regulation regarding the Contempt of Court through legislation. court officials themselves. In the Indonesian criminal law, the Contempt of Court has not been specifically regulated and the arrangements are scattered in several provisions of the Criminal Code article. However, in the context of reforming criminal law, especially in the Draft Criminal Code, the Contempt of Court is regulated in a separate chapter and formulated as a Crime Against Judicial Process which is a legal effort to defend the public interest and the rule of law so that the judicial process can be carried out fairly and fairly, without being disturbed. , influenced or undermined by other parties, both during the judicial process in court and outside the court building.